Digital comics learning media for high school on the human excretory system concept - Intan Nur Agustini; Sumiyati Sa'adah; Epa Paujiah (Universitas Muhammadiyah Malang, 2021)
Based on the preliminary analysis, one of the things needed in learning is a learning media that describes the material clearly, briefly, easily understood, and fulfills offline and online learning. This research aims to develop a digital comic learning media on the concept of the human excretory system. This study uses the R&D (Research and Development) method with the ADDIE model. The instruments in this study include a validation questionnaire, practicality test sheets, readability questionnaire, and student response questionnaire sheets to the developed digital comic learning media. The research data were analyzed quantitatively by calculating the percentage. The results showed that the digital comics learning media was valid and feasible to be used as learning media (combined average of 83%). The results of the student response test showed a very good response to the digital comic learning media with a percentage of 84%